Redescription of Bomis larvata L. Koch, 1874 with the description of a new Australian species - Szymkowiak, Paweł; Królikowska, Sylwia (Zootaxa, 2017)
All known species of Bomis are very small—spiders in this genus belong to the smallest crab spiders known. The type species, Bomis larvata L. Koch, 1874, is distributed in Australia. Three more species of the genus have been described from India. This paper is a redescription of B. larvata accompanied by a description of Bomis hippoponoi n. sp. from Australia.